Role of exchange interaction of identical particles of the discrete spectrum at simultaneous their tunneling through the potentia barrier dividing these particles - Martseniuk, L.S.; Maydanyuk, S.P.; Olhovsky, V.S. (Вопросы атомной науки и техники, 2009)
Work is devoted to theoretical research of influence of exchange interaction of identical particles on processes of simultaneous their tunneling through a rectangular potential barrier. Expression for exchange integral has been received and the analysis of dependence on parameters of identical particles and characteristics of a quantum barrier is lead. It is shown, that as including of exchange energy changes phase characteristics of the wave functions describing process of tunneling, exchange processes influence on the time characteristics of tunneling. Робота присвячена теоретичному дослідженню впливу обмінної взаємодії тотожних часток на процеси одночасного туннелювання їх через прямокутний потенційний бар'єр. Був отриманий вираз для обмінного інтеграла V й проведений аналіз залежності V від параметрів тотожних часток і характеристик квантового бар'єра. Показано, що, оскільки включення обмінної енергії змінює фазові характеристики хвильових функцій, що описують процес туннелювання, то обмінні процеси впливають на часові характеристики туннелювання. Работа посвящена теоретическому исследованию влияния обменного взаимодействия тождественных частиц на процессы одновременного туннелирования их через прямоугольный потенциальный барьер. Было получено выражение для обменного интеграла V и проведен анализ зависимости V от параметров тождественных частиц и характеристик квантового барьера. Показано, что, поскольку включение обменной энергии изменяет фазовые характеристики волновых функций, описывающих процесс туннелирования, то обменные процессы влияют на временные характеристики туннелирования.